Keefektifan Model PBL Bernuansa Etnomatematika Berbantuan E-LKPD Terhadap Kemampuan Pemecahan Masalah Siswa - Agita Nindi Sofiyani; Zaenuri (Circle: Jurnal Pendidikan Matematika, 2023)
This study aims to analyze the effectiveness of the e-LKPD assisted ethnomathematics PBL model on problem-solving skills and analyze the increase in students’ love of local culture after the implementation of the e-LKPD assisted ethnomathematics PBL model. Quantitative approach is used with the type of experimental research. The population of this study were class VII students of SMP Negeri 12 Semarang for the 2022/2023 academic year. By using cluster random sampling technique, class VII A and VII B were selected as the experimental and control classes. Methods of data collection is done by the method of tests, questionnaires, and documentation. Data were analyzed using one-group proportion test, one-group average test, twoproportion difference test, two-mean difference test, and paired t-test. The results showed that: (1) the problem-solving abilities of students who received an ethnomathematics nuanced PBL model assisted by e-LKPD achieved classical learning mastery and fulfilled the average achievement, the proportion of students' problem solving abilities with an ethnomathematics nuanced PBL model assisted by e-LKPD was more than the proportion problem-solving abilities of students with the PBL model, and the average problem-solving ability of students with the ethnomathematics nuanced PBL model assisted by e-LKPD is more than the average problem-solving ability of students with the PBL model, so it can be concluded that the e-LKPD assisted ethnomathematics PBL model is effective against students' problem solving abilities; (2) there is an increase in students' love for local culture after the implementation of the PBL model with an ethnomathematics assisted by e-LKPD.